Evidence of Common Isolates of Streptococcus agalactiae in Bovines and Humans in Emilia Romagna Region (Northern Italy) - Carra, Elena; Russo, Simone; Micheli, Alessia; Garbarino, Chiara; Ricchi, Matteo; Bergamini, Federica; Bassi, Patrizia; Prosperi, Alice; Piva, Silvia; Cricca, Monica; Schiavo, Roberta; Merialdi, Giuseppe; et al. (Frontiers in Microbiology, 2021)
Streptococcus agalactiae (group B Streptococcus, GBS) is one of the most important agents of bovine mastitis and causes remarkable direct and indirect economic losses to the livestock sector. Moreover, this species can cause severe human diseases in susceptible individuals. To investigate the zoonotic potential of S. agalactiae, 203 sympatric isolates from both humans and cattle, isolated in the same time frame (2018) and in the same geographic area (Emilia Romagna region, Northern Italy), were characterised by molecular capsular typing (MCT), pilus island typing (PI), and multi-locus sequence typing (MLST). In addition, antibiotic-resistant phenotypes were investigated. The distribution of the allelic profiles obtained by combining the three genotyping methods (MCT-PI-MLST) resulted in 64 possible genotypes, with greater genetic variability among the human compared to the bovine isolates. Although the combined methods had a high discriminatory power (>96,2%), five genotypes were observed in both species (20,9% of the total isolates). Furthermore, some of these strains shared the same antibiotic resistance profiles. The finding of human and bovine isolates with common genotypes and antibiotic resistance profiles supports the hypothesis of interspecies transmission of S. agalactiae between bovines and humans.